CRITERIA FOR EVALUATING INNOVATION ACTIVITY AND CHALLENGES IN DEFINING IT - A. T. Volkov (Ekonomika Nauki)
The article presents polemically the peculiarities of using the indicators of innovation activity for evaluating the state and outcomes of the organization’s operation, including Higher Learning Institutions in the areas of development and learning new types of techniques and technology. There is considered a possible structure of a system of balanced innovation activity indicators. There is substantiated a necessity to change statistical reporting on the innovation activity.